Antituberculosis drug-induced hepatotoxicity in children - Peter R. Donald (MDPI AG, 2011)
Recent increases in the dosages of the essential antituberculosis agents isoniazid (INH), rifampicin and pyrazinamide for use in children recommended by World Health Organization have raised concerns regarding the risk of hepatotoxicity. Published data relating to the incidence and pathogenesis of antituberculosis drug-induced hepatotoxicity (ADIH), particularly in children, is reviewed. Amongst 12,708 children receiving chemoprophylaxis, mainly with INH, but also other combinations of INH, rifampicin and pyrazinamide only 1 case (0.06%) of jaundice was recorded and abnormal liver functions documented in 110 (8%) of the 1225 children studied. Excluding tuberculous meningitis (TBM) 8984 were children treated for tuberculosis disease and jaundice documented in 75 (0.83%) and abnormal liver function tests in 380 (9.9%) of the 3855 children evaluated. Amongst 717 children treated for TBM, however, jaundice occurred in 72 (10.8%) and abnormal LFT were recorded in 174 (52.9%) of those studied. Case reports document the occurrence of ADIH in at least 63 children. Signs and symptoms of ADIH were frequently ignored in the recorded cases. Conclusion: ADIH is less common in children than adults, but can occur in children at any dosage of INH, RMP or PZA, but its incidence is considerably lower than in adults. Children with disseminated forms of disease are at greater risk of ADIH.